EU INTEGRATION POLICY: QUALIFIED MAJORITY VOTING (QMV) AND SUPRANATIONALITY COUNCIL OF MINISTERS - Muhammad Jave Zulkarnaen (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2021)
The European Union integration undergoes various long dynamic processes. Based on the views of academics, integration is defined as an effort to hand over all state functions to supranational organizations. The use of Qualified Majority Voting (QMV) is considered as an attempt to make the Council of Ministers a supranational institution. With the existence of QMV, member countries can no longer freely reject policies that are very likely to be carried out in the unanimous mechanism that has been implemented previously. After the implementation of the 2009 Lisbon Treaty, policymaking in the Council of Ministers will use the double majority mechanism which came into force on November 1, 2014. Basically, the double majority is an extension of the QMV mechanism by adding certain criteria in determining the majority of votes. There are three criteria that must be met in the double majority mechanism such as population criteria, supporting member countries criteria, and blocking criteria. The implication is that a country will find it difficult to unilaterally oppose the policies being discussed in the Council of Ministers. The reduced power of the state in the policy-making process indicates that the Council of Ministers continues to evolve towards a supranational institution. Based on these facts, the supranational of the Council of Ministers that develops through the use of the QMV mechanism will have a positive impact on the integration of the European Union as a whole.